Cofrades y devotos Estudios institucionales, sociales y económicos entre Andalucía y América (siglos XVI-XVIII) - Jiménez Jiménez, Ismael; López-Guadalupe Muñoz, Miguel Luis (Ariadna Ediciones, 2023)
This book brings together a good and varied number of studies on American devotions and brotherhoods, going to their models of origin, passing through the tools for the dissemination of specific devotions and offering research of an institutional, economic and social nature. But also, as you can read, these pages compile studies that are still open and that still have a long way to go, offering as many researchers as they wish an exciting and open field of work in History, Art History, Anthropology or the Right.